A apologia do objeto : experimentação e inovação formal na escultura modernista - Rosa, Ana Sofia da Cunha (2022)
The present dissertation seeks to approach the object as a relevant element and concept for the transformation of the sculptural tradition, which takes place mainly in the first half of the 20th century. In this period, Sculpture is subjected to an analysis of its meanings and conceptions and a radical change in the artistic panorama is transmitted. Thus, the proposed study intends to relate the expression of the object with the artistic attitude, which questions and develops the conventional typologies and characteristics, in order to solve threedimensionally a new sense of sculpture. We can observe that, in this avant-garde context, the appearance of the object appears as an alternative motif to the naturalism of the figure, which culminates in new sculptural results and in its expressive coincidence with representative processes that assume abstraction. In this way, it is intended to understand the object as a means of revolutionary proposals, which potentiate the development of the representative paradigm of Sculpture, as a pretext for formal experimentation and, consequently, na innovation of its meanings and concepts.